Perancangan Video Promosi Wana Wisata Batu Kuda Manglayang untuk Usia 17-25 Tahun di Kota Bandung - Sophia Purbasari; Muhamad Ikhsan Ramadhan; Meti Agni Rizkiani (ArtComm, 2024)
Batu Kuda Manglayang Nature Tourism, a forest managed by Perum Perhutani Kesatuan Pemangku Hutan (KPH) North Bandung, offers breathtaking natural beauty. However, tourist visits have declined due to insufficient promotion and the impact of the Covid-19 pandemic. This study aims to design an effective promotional strategy to increase tourist interest and awareness. The research method is qualitative, collecting data through interviews, observations, and questionnaires. The primary medium designed is a promotional video showcasing the natural beauty, facilities, and activities at Batu Kuda Manglayang Nature Tourism, with captivating cinematography. Supporting media such as posters, Instagram feed designs, and stickers are also prepared. It is hoped that this promotional strategy will attract tourist interest, raise awareness of the beauty of Batu Kuda Manglayang Nature Tourism, and revive the tourism sector. The goal is to establish Batu Kuda Manglayang Nature Tourism as a primary holiday destination in Bandung City, while also making a positive contribution to the economy and ecology of the area through social media.